ANALYSIS OF THE IMPLEMENTATION OF THE HOSPITAL MANAGEMENT INFORMATION SYSTEM (SIMRS) ON OPERATIONAL EFFICIENCY AT XYZ HOSPITAL PAMEKASAN - Seto Wahyu Prasetyo (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the implementation of the Hospital Management Information System (HMIS) and its impact on operational efficiency at XYZ Hospital in Pamekasan. In the digital era, hospitals are required to enhance service quality and operational efficiency through the utilization of information technology. HMIS is an innovation designed to integrate managerial and administrative processes within hospitals, including patient data recording, resource management, and other healthcare service procedures. This research adopts a descriptive qualitative approach with purposive sampling techniques, involving informants such as medical personnel, administrative staff, and hospital management who are directly involved in the use of HMIS.The results indicate that the implementation of HMIS has a positive impact on the hospital’s operational efficiency, including the acceleration of administrative processes, improved data accuracy, and easier coordination between work units. However, the implementation also faces several challenges, such as limited technological infrastructure, user resistance to change, and insufficient training for staff. These findings are supported by the HOT-Fit framework and Technology Acceptance Model (TAM), all of which emphasize the importance of technological readiness, human resource competence, and organizational commitment in ensuring the successful adoption of HMIS.